Spectroscopic Ellipsometry Studies and Temperature Behaviour of the Dielectric Function of TlInS2 Layered Crystal - O.O.В Gomonnai; O.В Gordan; P.P.В Guranich; P.В Huranich; A.G.В Slivka; A.V.В Gomonnai; D.R.T.В Zahn (Журнал нано- та електронної фізики)
Real and imaginary parts of the dielectric function of TlInS2 single crystals in the spectral range from 1 to 5 eV were determined within a temperature range of 133вЂ“293В K from spectroscopic ellipsometry measurements. The energies of interband transitions (critical points) for TlInS2 were obtained from the second derivatives of the dielectric function. Temperature dependent features observed in the temperature range of the structural phase transition (190вЂ“220 K) and at lower temperatures are discussed.